THE USE OF ADAPTIVE AND INTELLECTUAL EDUCATIONAL TECHNOLOGIES IN TRAINING OF MODERN SPECIALISTS - Bakhov, I. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
In the development of educational software, there are ongoing dynamic changes that affect the market of educational services on the Internet. The current state of the distance education system requires the latest educational technology to effectively meet the needs of students who study virtually. The article defines how intelligent systems are used in the training of modern specialists through the system of distance learning.Adaptive and intelligent Web-based educational systems form a new and exciting stream of work in AI-Ed field. The paper demonstrates that the Web offers an opportunity to apply a much larger variety of AI technologies in educational context. It offers a number of new research challenges and a number of opportunities to fuse AI-Ed research with several neighboring fields. The Web also provides an excellent implementation platform for AI- Ed researchers. Systems developed on the Web have longer lifespan and better visibility. A research idea implemented in a Web-based system has much better chances to influence the research community than an idea simply presented in a paper. Adaptive and intelligent Web-based educational systems provide an alternative to the traditional “just-put-it-on-the-Web” approach in the development of Web-based educational courseware.The goal of the article is to provide a more systematic view to the variety of modern AIWBES and to discuss the role and the place of the AIWBES research stream in the field of Artificial Intelligence in Education. The reason to focus on both intelligent and adaptive systems is that the intersection is still large, the borders between “intelligent” and “non-intelligent” are not clear-cut, and both groups are certainly of interest for AI in Education (AI-Ed) community. By adaptive and intelligent technologies we mean essentially different ways to add adaptive or intelligent functionality to an educational system. A technology usually can be further dissected into finer-grain techniques and methods, which correspond to different variations of this functionality and different ways of its implementation.
Keywords: educational systems, intellectual systems, student, internet, hypermedia